Time-Independent Data Collection Protocol in Mobility-Assistant Wireless Sensor Networks with Duty Cycles. (10th May 2012) - Zhang, Xiwei; Xu, Lijie; Chen, Guihai
Abstract : Mobility-assistant sensor networks comprise mobile elements, and static sensors are established for the purpose of solving the serious problems such as overlapping or energy holes in wireless sensor networks (WSNs). In such systems, most of the energy is consumed when the radios are on, waiting for a mobile sink (MS) to arrive. Sleep/wake scheduling is an effective mechanism to prolong the lifetime of these energy-constrained wireless sensors. However, sleep/wake scheduling could result in substantial discovery delays because the sensor needs time to receive the beacon-ID signals when MS entered its communication range. In this paper, we first study on the MS discovery mechanism and the factors which affect the efficiency of data collection. Based on these results, we then provide a solution to the control problem of how to optimally adjust the system parameters of the sleep/wake scheduling protocol to maximize the network lifetime, subject to a constraint on the expected residual contact time. Our numerical results indicate that the proposed solution can balance the network consumption, especially in sparse sensor networks.